Back Cover: Nucleus‐specific RNAi nanoplatform for targeted regulation of nuclear lncRNA function and effective cancer therapy (EXP2 5/2022). Issue 5 (21st October 2022) - Huang, Zixian; Liu, Shaomin; Lu, Nan; Xu, Lei; Shen, Qian; Huang, Zhuoshan; Huang, Zhiquan; Saw, Phei Er; Xu, Xiaoding
Abstract : A nucleus‐specific RNAi nanoplatform was developed by Xu et al. for targeted regulation of nuclear lncRNA function and effective cancer therapy. This nanoplatform could respond to the endosomal pH to expose NTPA/siRNA complexes for the nucleus‐specific siRNA delivery, leading to a significant inhibition of nuclear lncNEAT2 expression and tumor growth.